2016
DOI: 10.1155/2016/4823630
|View full text |Cite
|
Sign up to set email alerts
|

Management of Highway Projects in Egypt through Identifying Factors Influencing Quality Performance

Abstract: While project management success focuses upon the processes and the successful accomplishments of cost and time objectives, product success deals with the quality of the final product. Recently, quality of the constructed highway has been considered highly important reason for the pavement response and its design life. The main objective of this paper is to improve the management of highway projects in Egypt by determining the most important factors influencing the quality performance of this industry. In tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…In previous studies, it has been found that the successful completion of project objectives and success deals with the quality of the final product [19][20][21]. Indeed, factors affecting the quality of construction projects have been identified in previous studies such as Arditi and Gunaydin [22], who classified factors, for example, management commitment to continuous quality improvement, personnel training, efficient and effective teamwork among and between parties involved in the project, as common factors that affected project process quality.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, it has been found that the successful completion of project objectives and success deals with the quality of the final product [19][20][21]. Indeed, factors affecting the quality of construction projects have been identified in previous studies such as Arditi and Gunaydin [22], who classified factors, for example, management commitment to continuous quality improvement, personnel training, efficient and effective teamwork among and between parties involved in the project, as common factors that affected project process quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mandal et al [28] developed a quality process model combining the human resources, technical, and quality improvement system, where the human resources factor was found as one of the three subsystems affecting the quality. Rustom and Amer [19] used a fuzzy triangle methodology and revealed that the most significant parameters influencing the quality of projects were skilled and experienced personnel in the teams of both the owner and contractor and the efficiency of the owner's assessment team. Furthermore, construction quality could be improved by increasing the skilled and experienced labor on a project site [29].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It will stay inside the pavement structure, weaken the strength of the base layer and the subgrade, accelerate the road damage, and reduce the driving quality [2,3]. rough investigation, it was found that the construction quality issue of asphalt layer is an important reason for the lowtemperature cracking of asphalt pavement [4,5]. e construction process control of the asphalt layers is mainly conducted according to the asphalt pavement construction specifications [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Abdul-Razak et al (2010) stated that certain construction projects in Malaysia fail to achieve client's satisfaction on quality level. It is quoted by El-Maaty et al (2016) that according to the reports of World Bank, only 20% of road projects in Egypt are at the desired level of quality.…”
Section: Introductionmentioning
confidence: 99%